Ethnobotanical Survey on Medicinal Plants used by the Manobo Tribe of Don Marcelino, Davao Occidental, Philippines - Cabugatan, May Ann Diamante; Ong, Rona Lynn Jane Tundag; Mancao, Liezl Sumilhig; Lumogdang, Leonel Patoc (Asian Journal of Biological and Life Sciences)
Ethnobotanical knowledge has been instrumental in the identification of new potent sources of novel bioactive compounds. Hence, ethnobotanical study is highly essential as a precursor for drug discovery. The study aimed to document the medicinal plants used by the Manobo tribe of Don Marcelino, Davao Occidental Philippines. In this study, the ethnobotanical practices of the Manobo tribe were explored and surveyed from the three (3) Barangay of Don Marcelino, Davao Occidental Philippines. The study employed observational-descriptive surveys in data gathering. Structured interviews using questionnaires were also utilized in the study. A total of 30 respondents were interviewed with ages between 21-46 years old and above. Based on the results, there were forty-one (41) medicinal plants identified by the Manobo tribe belonging to the twenty-eight (28) taxonomic families. Psidium guajava is the most cited while Moringa oleifera has the highest used value. Leaves are the most utilized parts and are prepared by decoction to extract the curative compounds of the medicinal plants. Furthermore, studies on the screening of novel compounds are highly desirable to additionally substantiate the medicinal properties of each identified plant.
Keywords: Ethnobotany; Knowledge; Manobo; Medical; Traditional